Implementation of a pilot community-based psychosocial intervention for patients with psychoses in Chile and Brazil: a comparative analysis of users' perspectives. (27th April 2021) - Dev, Saloni; Kankan, Tanvi; Blasco, Drew; Le, PhuongThao D.; Agrest, Martin; Dishy, Gabriella; Mascayano, Franco; Schilling, Sara; Jorquera, María José; Dahl, Catarina; Cavalcanti, Maria Tavares; Price, LeShawndra; et al.
Abstract: Background: Few studies provide clear rationale for and the reception of adaptations of evidence-based interventions. To address this gap, we describe the context-dependent adaptations in critical time intervention-task shifting (CTI-TS), a manualized recovery program for individuals with psychosis in Rio de Janeiro, Brazil and Santiago, Chile. Implications of the adaptations – incorporating a task-shifting approach and modifying the mode of community-based service delivery – are examined from users' perspectives. Methods: A secondary analysis of in-depth interviews with CTI-TS users ( n = 9 in Brazil; n = 15 in Chile) was conducted. Using the framework method, we thematically compared how participants from each site perceived the main adapted components of CTI-TS. Results: Users of both sites appreciated the task-shifting worker pair to provide personalized, flexible, and relatable support. They wanted CTI-TS to be longer and experienced difficulty maintaining intervention benefits in the long-term. In Chile, stigma and a perceived professional hierarchy toward the task-shifting providers were more profound than in Brazil. Engagement with community-based services delivery in homes and neighborhoods (Chile), and at community mental health centers (Brazil) were influenced by various personal, familial, financial, and social factors. Uniquely, community violence was a significant barrier to engagement in Brazil. Conclusion: CTI-TS' major adaptations were informed by the distinct mental health systems and social context of Santiago and Rio. Evaluation of user experiences with these adaptations provides insights into implementing and scaling-up task-shifting and community-oriented interventions in the region through the creation of specialized roles for the worker pair, targeting sustained intervention effects, and addressing socio-cultural barriers.